Analisis Perbandingan Inflasi dalam Perspektif Islam dan Konvensional - Fitri Kurniawati; Nurwahidin (Syntax Idea)
This study analyzes the comparison of inflation based on Islamic and conventional perspectives. The study was conducted using a qualitative method based on information in the literature such as text books or scientific research journals. The problem of inflation is a macroeconomic phenomenon that has yet to be resolved. Inflation is defined as the trend of general price increase over time in an economy. Both conventional economics and Islamic economics acknowledge the existence of inflation even though there are differences in some of the causes, but both of these approaches recognize that inflation comes from an increase in aggregate demand and an excess money supply. Meanwhile, the differences between inflation under conventional perspective and inflation under Islamic perspective show the essence differences between conventional economics and Islamic economics. Most of these determinants of inflation are systemic errors invented by contemporary conventional economic and finance that have the potential to be corrected or replaced by proper alternative systems. The Islamic economic system which prohibits usury, maysir, gharar can fix the determinants of inflation originating from the conventional economy.